Vulnerability of land use/cover associated with human-wildlife conflicts in Mullaitivu District, Sri Lanka - Bharathy, P.; Wijeyamohan, S.; Suthakar, K.; Surendran, S.N. (Taylor & Francis Group, 2022)
Human-wildlife conflict has increased over the decades and is now considered one of the most severe challenges to the survival of threatened species and the livelihood of communities world wide. In Sri Lanka, population growth, fragmentation of land, and conversion of natural wildlife habitats into settlement and agricul tural areas are the leading causes of human-wildlife conflict. This study seeks to characterise the conflict pattern in the Mullaitivu District by identifying land use/cover changes and assessing the vulnerability of land use/cover. Primary data were collected through a field survey using a structured questionnaire and direct observation methods, and secondary data on land use/cover changes were obtained from remote sensing images. These data were analysed statistically and on the Geographic Information System (GIS) platform. The study reveals land use/cover vulner ability status over the twenty-six years. Dense forests are on the decline, and wild animals migrate into human settlements and agricultural sites, resulting in different types of human-wildlife conflict such as crop damage, livestock depredation, and loss of life and/or injuries to both people and wildlife in the Mullaitivu district. People employ various wildlife mitigation strategies. However, they cannot safeguard their crops or livestock from these animals. By implementing appropriate management meas ures to avoid wildlife infiltration into human settlements, the human-wildlife conflict in the Mullaitivu district can be minimised.
Keywords: Remote sensing and GIS; Human-wildlife conflict; Land use/cover change; Mullaitivu district